(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research was conducted to determine the effect of business ethics (cooperation, adherence to work regulations, integrity, transparency, and mastery) on the performance of human resources, in private universities operating in the Syrian coast. The researcher distributed (120) questionnaires to a sample of managers and workers at the universities under study. (109) questionnaires were retrieved and (7) questionnaires were excluded, Thus, the number of questionnaires that have been discharged is (102). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which are: There is a significant effect of business ethics (cooperation, adherence to work regulations, integrity, transparency, and mastery) on the performance of human resources at the universities under study. The researcher also made a number of recommendations, including: The need for the universities under study to continuously analyze their internal environment in order to identify weaknesses and strengths in them, and the need to identify individuals who have the experience, skill, high efficiency and appropriate to analyze the environment, and the need to pay attention to ethical standards as well as efficiency standards in order to achieve the goals of the organization.